The evaluation of myofiber remodeling and skeletal muscle inflammaging using a novel guinea pig model - Walsh, Maureen Ann, author; Hamilton, Karyn L., advisor; Lark, Daniel S., committee member; Reiser, Raoul F., II, committee member; Santangelo, Kelly S., committee member (Colorado State University. Libraries, 2020)
Approximately 40% of total body mass is accounted for by the musculoskeletal system and thus, when it becomes dysfunctional it strongly influences whole body function. Sarcopenia is one facet of musculoskeletal aging and contributes to other age-related chronic diseases. Aging is a major risk factor for osteoarthritis, which is characterized by a concomitant loss of skeletal muscle, further contributing to decreased mobility. Age-related increases in low-grade inflammation and oxidative stress, referred to as the "inflammaging" phenotype, is common to both osteoarthritis and sarcopenia. While we have begun to understand the underlying pathology of sarcopenia, treatments are still lacking. One barrier to progress in identifying treatments is lack of a preclinical model that recapitulates the human skeletal muscle aging phenotype. Dunkin Hartley guinea pigs rapidly and spontaneously develop primary osteoarthritis beginning at about 4 months of age. The purpose of these studies was to determine if the Dunkin Hartley guinea pig can serve as a model to understand human skeletal muscle aging. Thus, we speculate that the Dunkin Hartley guinea pig may also be a valuable model of myofiber remodeling and skeletal muscle inflammaging. We compared skeletal muscle myofiber properties of the gastrocnemius and soleus from 5, 9, and 15-month Dunkin Hartley guinea pigs. We also compared these changes to a strain of guinea pig, Strain 13, that does not develop knee osteoarthritis at an early age. Additionally, in a second study, we assessed markers of skeletal muscle inflammation, oxidatively modified proteins, and redox signaling in 5 and 15-month Dunkin Hartley guinea pigs. The Dunkin Hartley guinea pig showed evidence of skeletal muscle aging including declines in gastrocnemius density and a shift in myofiber size distribution to encompass a greater percentage of smaller myofibers in both the gastrocnemius and soleus. Male Dunkin Hartley guinea pigs experience a trend to decrease Nrf2 protein content from 5 to 15-months implying altered redox signaling, while female Dunkin Hartley guinea pigs experienced a significant increase from 5 to 15-months. Skeletal muscle myofiber remodeling, a component of musculoskeletal aging, influences both muscle function and quality of life. Based on these analyses, Dunkin Hartley guinea pigs appear to be a potentially valuable model of musculoskeletal aging.